The Function of Phatic Language in The Novel Samuel by Itakrn - Zahra; Gazali (Universitas Islam Negeri Palopo, 2025)
This study aims to analyze the phatic function of language in Itakrn's novel Samuel. This research was conducted using qualitative descriptive research with the content analysis method. The researcher focused this research using Roman Jakobson's language function theory which states that the phatic function of language consists of four parts, namely: conversation starters, conversation continuation, conversation closings, and expressions in casual chats. The data source for this study was obtained from Itakrn's novel Samuel, the second edition in April 2022 published by PT Akad Media Cakrawala in 2022. Data collection in this study used reading and note-taking techniques. The results of this study indicate that there are four parts of the phatic function in Itakrn's novel Samuel.